Exposure to low dose ZnO nanoparticles induces hyperproliferation and malignant transformation through activating the CXCR2/NF-κB/STAT3/ERK and AKT pathways in colonic mucosal cells. (August 2020) - Meng, Jian; Zhou, Xiaoling; Yang, Juan; Qu, Xianjun; Cui, Shuxiang
Abstract: As ZnO nanoparticles have been applied in many fields, their biological risks on human health, of course, are worthy of our attention. Whether ZnO NPs have the risk and how colonic cells respond to the invaded ZnO NPs are still unknown. Herein, we evaluated the biological effects of ZnO NPs on colonic mucosal cells by in vitro and in vivo methods. IMCE cells, with APC mutation but phenotypically normal, demonstrated hyperproliferation through activating the CXCR2/NF-κB/STAT3/ERK and AKT pathways when exposed to ZnO NPs for 24 h. Long-term exposure of ZnO NPs resulted in the malignant transformation of IMCE cells, showing the morphological changes, anchorage-independent cell growth ability. Importantly, IMCE cells exposed to ZnO NPs subcutaneously grew and induced tumorigenesis in nude mice. In conclusion, exposure of ZnO NPs could induce malignant transformation of colonic mucosal cells through the CXCR2/NF-κB/STAT3/ERK and AKT pathways. We suggest that it was necessary to consider using the precautionary principle for gastrointestinal contact nanomaterials. Graphical abstract: Image 1 Highlights: Exposure of low-dose ZnO NPs induces cell hyperproliferation. Long-term exposure of ZnO NPs induces tumorigenesis. ZnO NPs activates the CXCR2/NF-κB/STAT3/ERK and AKT pathways. Zinc ions and NPs are functional forms of ZnO NPs.